Longitudinal Invariance Testing Of The Knee Injury Osteoarthritis Outcome Score For Joint Replacement Scale (KOOS-JR) - Alexandra Dluzniewski; Caleb Allred; Madeline P Casanova; Jonathan D Moore; Adam C Cady; Russell T Baker (International Journal of Sports Physical Therapy)
# Background